Coupling biocatalysis with high-energy flow reactions for the synthesis of carbamates and β-amino acid derivatives - Leslie, Alexander; Moody, Thomas S.; Smyth, Megan; Wharry, Scott; Baumann, Marcus (Beilstein Journal of Organic Chemistry, 2021)
A continuous flow process is presented that couples a Curtius rearrangement step with a biocatalytic impurity tagging strategy to produce a series of valuable Cbz-carbamate products. Immobilized CALB was exploited as a robust hydrolase to transform residual benzyl alcohol into easily separable benzyl butyrate. The resulting telescoped flow process was effectively applied across a series of acid substrates rendering the desired carbamate structures in high yield and purity. The derivatization of these products via complementary flow-based Michael addition reactions furthermore demonstrated the creation of β-amino acid species. This strategy thus highlights the applicability of this work towards the creation of important chemical building blocks for the pharmaceutical and speciality chemical industries.
Keywords: biocatalysis; CALB; Curtius rearrangement; flow synthesis; reaction telescoping

(untitled) - Baumann, M.; Moody, T. S.; Smyth, M.; Wharry, S. (Org. Process Res. Dev., 2020)

(untitled) - Gioiello, A.; Piccinno, A.; Lozza, A. M.; Cerra, B. (J. Med. Chem., 2020)

(untitled) - Guidi, M.; Seeberger, P. H.; Gilmore, K. (Chem. Soc. Rev., 2020)

(untitled) - Jensen, K. F. (AIChE J., 2017)

(untitled) - Burcham, C. L.; Florence, A. J.; Johnson, M. D. (Annu. Rev. Chem. Biomol. Eng., 2018)

(untitled) - Baumann, M.; Moody, T. S.; Smyth, M.; Wharry, S. (Eur. J. Org. Chem., 2020)

(untitled) - Gérardy, R.; Emmanuel, N.; Toupy, T.; Kassin, V.-E.; Tshibalonza, N. N.; Schmitz, M.; Monbaliu, J.-C. M. (Eur. J. Org. Chem., 2018)

(untitled) - McWilliams, J. C.; Allian, A. D.; Opalka, S. M.; May, S. A.; Journet, M.; Braden, T. M. (Org. Process Res. Dev., 2018)

(untitled) - Cranwell, P. B. (SynOpen, 2020)

(untitled) - Britton, J.; Raston, C. L. (Chem. Soc. Rev., 2017)

(untitled) - Movsisyan, M.; Delbeke, E. I. P.; Berton, J. K. E. T.; Battilocchio, C.; Ley, S. V.; Stevens, C. V. (Chem. Soc. Rev., 2016)

(untitled) - Gutmann, B.; Cantillo, D.; Kappe, C. O. (Angew. Chem., Int. Ed., 2015)

(untitled) - Dallinger, D.; Gutmann, B.; Kappe, C. O. (Acc. Chem. Res., 2020)

(untitled) - Baumann, M. (Org. Biomol. Chem., 2018)

(untitled) - Weeranoppanant, N.; Adamo, A. (ACS Med. Chem. Lett., 2020)

(untitled) - Rogers, L.; Briggs, N.; Achermann, R.; Adamo, A.; Azad, M.; Brancazio, D.; Capellades, G.; Hammersmith, G.; Hart, T.; Imbrogno, J.; Kelly, L. P.; Liang, G.; et al. (Org. Process Res. Dev., 2020)

(untitled) - Yuryev, R.; Strompen, S.; Liese, A. (Beilstein J. Org. Chem., 2011)

(untitled) - Britton, J.; Majumdar, S.; Weiss, G. A. (Chem. Soc. Rev., 2018)

(untitled) - Tamborini, L.; Fernandes, P.; Paradisi, F.; Molinari, F. (Trends Biotechnol., 2018)

(untitled) - Leemans Martin, L.; Peschke, T.; Venturoni, F.; Mostarda, S. (Curr. Opin. Green Sustainable Chem., 2020)

(untitled) - Baumann, M.; Leslie, A.; Moody, T. S.; Smyth, M.; Wharry, S. (Org. Process Res. Dev., 2021)

(untitled) - Baumann, M.; Baxendale, I. R.; Ley, S. V.; Nikbin, N.; Smith, C. D.; Tierney, J. P. (Org. Biomol. Chem., 2008)

(untitled) - Guetzoyan, L.; Ingham, R. J.; Nikbin, N.; Rossignol, J.; Wolling, M.; Baumert, M.; Burgess-Brown, N. A.; Strain-Damerell, C. M.; Shrestha, L.; Brennan, P. E.; Fedorov, O.; Knapp, S.; et al. (MedChemComm, 2014)

(untitled) - Filipponi, P.; Ostacolo, C.; Novellino, E.; Pellicciari, R.; Gioiello, A. (Org. Process Res. Dev., 2014)

(untitled) - Connor, C. G.; DeForest, J. C.; Dietrich, P.; Do, N. M.; Doyle, K. M.; Eisenbeis, S.; Greenberg, E.; Griffin, S. H.; Jones, B. P.; Jones, K. N.; Karmilowicz, M.; Kumar, R.; et al. (Org. Process Res. Dev., 2021)

(untitled) - Shen, J.-W.; Qi, J.-M.; Zhang, X.-J.; Liu, Z.-Q.; Zheng, Y.-G. (Org. Process Res. Dev., 2019)

(untitled) - Cassimjee, K. E.; Hendil-Forssell, P.; Volkov, A.; Krog, A.; Malmo, J.; Aune, T. E. V.; Knecht, W.; Miskelly, I. R.; Moody, T. S.; Svedendahl Humble, M. (ACS Omega, 2017)

(untitled) - Cen, Y.; Singh, W.; Arkin, M.; Moody, T. S.; Huang, M.; Zhou, J.; Wu, Q.; Reetz, M. T. (Nat. Commun., 2019)

(untitled) - Lee, J.; Kim, M.-h.; Jew, S.-s.; Park, H.-g.; Jeong, B.-S. (Chem. Commun., 2008)